Comparative analysis of six nutritional scores in predicting prognosis of COVID-19 patients - Zou, Shangpu; Lin, Pengcheng; Chen, Xiaoyu; Xia, Lijing; Liu, Xiling; Su, Shanshan; Zhou, Ying; Li, Yuping (Frontiers in Nutrition, 2024)
Background: Identifying nutritional risk in COVID-19 patients poses a challenge due to the unique qualities of every nutritional screening instrument. The objective was to assess the efficacy of six nutritional scores, including the Nutritional Risk Screening 2002 (NRS-2002) score, the NUTRIC (nutrition risk in the critically ill) score, the modified NUTRIC score, the prognostic nutritional index(PNI),controlling nutritional status (CONUT) score, TCB index (TCBI),predicting prognosis of COVID-19 patients. Methods:Clinical data were collected from COVID-19 patients admitted to the First Affiliated Hospital of Wenzhou Medical University between December 2022 and February 2023. Participants in this research were divided into two groups: all patients and those specifically from the intensive care unit (ICU). Each group was further stratified into two groups: survivors and non-survivors. Result: 506 COVID-19 patients and 190 COVID-19 patients in intensive care unit (ICU) were evaluated. In all COVID-19 patients, we found that NRS-2002 (p < 0.001) and TCBI (p = 0.002) were statistically significant independent predictors in multivariate analyses, while APACHE II score(p =0,048) and the mNUTRIC score (p = 0.025) were statistically significant independent predictors in multivariate analyses in ICU patients. The NRS-2002 demonstrated a higher AUC value (0.687) than other nutritional scores in all patients, with an optimum cut-off value of 3, translating into a corresponding sensitivity of 66.2% and specificity of 68.7%. With an optimum cutoff value of 4, the mNUTRIC score demonstrated a higher AUC value (0.884) in ICU patients, resulting in a sensitivity of 88.4% and a specificity of 76.9%. By using the discrimination and clinical application (DCA) curve, NRS-2002 demonstrated the greatest net benefit in all patients, while NUTRIC score and mNUTRIC score offered the more significant overall advantage than other nutritional scores in ICU patients. Kaplan-Meier analyses showed lower survival rates in patients in low nutritional risk . Conclusions: Malnutrition was common in COVID-19 patients. The mNUTRIC score and NRS-2002 were respectively more effctive scoring systems of prognosis in all COVID-19 patients and severe or critical COVID-19 patients of the intensive care unit (ICU).